Biodiversity means business: Reframing global biodiversity goals for the private sector. Issue 1 (4th December 2019) - Smith, Thomas; Beagley, Lucy; Bull, Joseph; Milner‐Gulland, E. J.; Smith, Matt; Vorhies, Francis; Addison, Prue F. E.
Abstract: The Convention on Biological Diversity strategic goals direct the conservation and sustainable use of biodiversity from global to local scales. Yet business' role in meeting the strategic goals and being accountable for their impacts and dependencies on biodiversity are still not fully and coherently outlined. We demonstrate how business actions can contribute to the strategic goals using 10 publicly available case studies, covering businesses of various sizes, from multiple sectors, operating in different contexts. The case studies show some businesses already contribute to meeting biodiversity goals, often without realizing. We consider the drivers of business engagement with biodiversity; problems in interpreting the scale of impacts through corporate reporting; the implications for changing the way businesses engage with biodiversity goals; and how businesses could contribute more under the post‐2020 framework for biodiversity. We call for increased business accountability for nature and that all in conservation—policymakers, practitioners, researchers, communities—do more to connect businesses with the strategic goals. Clearer business roles and responsibilities within international targets form a critical step toward the fundamental systems‐level change required to reverse biodiversity loss.